Anna Gabriella e a autoetnografia: narrativas sobre a influência de Harry Potter e o movimento feminista no processo de construção identitária - Almeida, Anna Gabriella Cavalcante Mamede de (2021)
The interest for this research emerged because of the process about meaning making regarding standard practices that regulate women’s performance. To produce such a discussion three items from the list “Aprenda 10 dicas para conquistar um homem” were selected. The methodology used for this research was autoethnography (ONO, 2017) (ADAM; JONES; ELLIS, 2015) and consisted of proposing a reflexivity (ADAM; JONES; ELLIS, 2015) about how my identity construction influences my apprehension about the three selected items. An autoethnographic research intends to connect researchers with cultural experiences and readers. This way, in this investigation I share my personal experiences to understand how my identity was developed. So, my relationship with the Harry Potter saga and feminist movement were the two perspectives chosen to understand their influence in my identity construction. By observing these two contexts it was possible to comprehend how I produce meaning about the three selected items from the list “Aprenda 10 dicas para conquistar um homem”. Concepts about how readers are capable of developing civic imagination (JENKINS, LAZARO, SHRESTHOVA, 2020) by consuming pop culture products helped to understand my relationship with the Harry Potter saga. Then, it was necessary to consider my feminist identity using the ideas of the feminist movements organized in Brazil (TELLES, 1993) (PINTO, 2003). Those ideals allowed me to comprehend that my discomfort when reading the three selected items arose because they made me feel emotions. The final reflections point that, even though I try to rationalize my feelings, my emotions are manifested in social injustice situations.